2016
DOI: 10.1080/15384101.2016.1222336
|View full text |Cite
|
Sign up to set email alerts
|

PICH promotes mitotic chromosome segregation: Identification of a novel role in rDNA disjunction

Abstract: PICH is an SNF2-family DNA translocase that appears to play a role specifically in mitosis. Characterization of PICH in human cells led to the initial discovery of "ultra-fine DNA bridges" (UFBs) that connect the 2 segregating DNA masses in the anaphase of mitosis. These bridge structures, which arise from specific regions of the genome, are a normal feature of anaphase but had escaped detection previously because they do not stain with commonly used DNA dyes. Nevertheless, UFBs are important for genome mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…A recent study has revealed that PICH has a role in attracting and activating the decatenase activity of TOP2A at highly repetitive loci, such as at rDNA and centromeric regions 158 . Following this work, it has been shown that, similar to centromeric DNA, rDNA may also undergo delayed decatenation and form PICH-stained anaphase bridges, which are induced by Topoisomerase II inhibition, thus identifying another class of UFBs 159 . Other clues regarding the nature and origin of UFBs have come from the identification of additional proteins that bind to these structures and are important for their resolution, including TOP2A, Topoisomerase IIβ-binding protein 1 (TopBP1), FANCM and Rif1.…”
Section: Anaphase Bridgesmentioning
confidence: 81%
“…A recent study has revealed that PICH has a role in attracting and activating the decatenase activity of TOP2A at highly repetitive loci, such as at rDNA and centromeric regions 158 . Following this work, it has been shown that, similar to centromeric DNA, rDNA may also undergo delayed decatenation and form PICH-stained anaphase bridges, which are induced by Topoisomerase II inhibition, thus identifying another class of UFBs 159 . Other clues regarding the nature and origin of UFBs have come from the identification of additional proteins that bind to these structures and are important for their resolution, including TOP2A, Topoisomerase IIβ-binding protein 1 (TopBP1), FANCM and Rif1.…”
Section: Anaphase Bridgesmentioning
confidence: 81%
“…Accordingly, mitotic chromosome segregation is tightly monitored by the mitotic checkpoint that delays the irreversible chromosome segregation until the chromosomes are correctly attached to the mitotic spindle, each sister chromatid pair having stable attachments to both poles of the mitotic spindle through their kinetochore complexes at the centromeric region. Even though the cell division cycle is a tightly controlled, errors in chromosome segregation occur, especially in cancer cells 32 . Chromosome segregation errors detectable in anaphase, such as lagging chromosomes, chromatin bridges, and acentric chromatin fragments, can be caused by incomplete chromosome replication, telomere attrition, unresolved DNA damage repair intermediates and intertwined sister chromatids resulting from replication stress in the S phase of the cell division cycle or incorrect kinetochore-microtubule attachments frequently established during early mitosis 30,[33][34][35][36] .…”
mentioning
confidence: 99%
“…The rDNA loci also occasionally give rise to PICH-and TopIIα-decorated R-UFBs ( Fig. 1B; Nielsen and Hickson 2016). The number of R-UFBs increases following inhibition of TopIIα by .…”
Section: Ufbs At Telomeresmentioning
confidence: 94%
“…RUFBs are also induced by and are thought to arise because of the late condensation of the rDNA locus hindering decatenation (Nielsen and Hickson 2016). Considering that TopIIα is a dsDNA-specific enzyme, this implies that the majority of C-UFBs and R-UFBs are completely double-stranded catenanes (Fig.…”
Section: Modeling Ufbs Using Ensemble Biochemistrymentioning
confidence: 99%